Seed mycofloras of hyacinth beans (Lablab niger) and long beans (Vigna sesquipedalis) and their pathogenic importance - Kanapathipillai, Vijaya S. (British Mycological Society, 1982)
Isolations and identifications of seed-borne fungi from two seed lots of Lablab niger and Vigna sesquipedalis seed were made. Among the various species of fungi isolated, Curvularia sp., Drechslera sativum, Diplodia sp., Chaetomium globosum, Pestalotiopsis sydowiana, Aspergillus spp. and Fusarium spp. were the most common on these two beans. Nigrospora sacchari and Phyllosticta sp. were confined to L. niger. Macrophomina phaseolina and Colletotrichum sp. were found only on V. sesquipedalis. Selected fungi were isolated, and tested for pathogenicity to emerging seedlings and established seedlings of L. niger and V. sesquipedalis. Phyllosticta sp., Diplodia sp., Drechslera sativum and Macrophomina phaseolina were found to be pathogenic. The pathological importance of these fungi is further discussed.